The Effect of Clil Training on Turkish Efl Pre-Service Teachers’ Self-Efficacy Beliefs and Attitudes Towards Clil - Kassymov, Guzyal; Çiftçi, Hatime (E.L.E. Publishing, 2020)
This study aims to investigate the effect of content and language integrated learning (CLIL) training on Turkish EFL pre-service teachers’ self-efficacy beliefs and their attitudes towards CLIL. For this purpose, a group of 28 Turkish pre-service language teachers was trained on CLIL, its theoretical background, aims, principles, strategies for planning and teaching lessons. The data collection tools included a teacher selfefficacy scale, a questionnaire of attitudes and experiences in CLIL, and semistructured interviews. The participants completed pre-tests and post-tests of teacher self-efficacy scale in order to measure the effect of training on their self-efficacy beliefs. Moreover, the participants’ attitudes towards CLIL were explored through the attitudes questionnaire and semi-structured face-to-face interviews. The findings revealed that the introductory CLIL teacher training had a statistically significant effect on selfefficacy beliefs of Turkish EFL pre-service teachers. The participants’ attitudes towards CLIL turned out to be positive as well.
Keywords: English language teaching; Teacher self-efficacy beliefs; Teacher training; CLIL